Caracterização da microestrutura de concretos estruturais antigos de barragem: estudo de caso da hidrelétrica de Paulo Afonso IV - PA IV - Henriques, Glauco Fonsêca (2022)
Among the various construction materials, concrete stands out as the most used worldwide. Historically, among the main types of works using concrete, stand out hydraulic structures such as dams and hydroelectric plants. The durability and performance of concrete in these works is affected by the accumulation of damage induced by external charging in conjunction with environmental effects, such as surface erosion, calcium leaching, sulfate attack, alkali-aggregate reactions, steel corrosion, etc. Several studies on the ability of concrete to resist deterioration have been conducted under standardized laboratory conditions, but it is complex to compare their results with the performance of field concrete, since the time periods of these studies are short compared to the lifetime of hydraulic works. Thus, in order to analyze and characterize old concrete taken from the Paulo Afonso IV (PA IV) dam, the objective of this work is to evaluate the microstructure of the dam's drilled cores by microscopy (SEM), spectroscopy (EDS), surface zoning analysis (MAZE) and comparative x-ray diffraction (XRD), highlighting phases, compositions, products found, differences in relation to the depth of extraction, etc. Five samples from three different extraction holes from PA IV dam were analyzed, these at least 40 years old. The microstructural results and discussions show the presence of alkaline aggregate phases, a cement matrix with diversified calcium aluminates and calcium silicates, cracking and pores of various sizes, and regions of ettringite concentration.